Ixodid Tick Vectors of Wild Mammals and Reptiles of Southern India - K. G. Ajith Kumar; Reghu Ravindran; Joju Johns; George Chandy; Kavitha Rajagopal; Leena Chandrasekhar; Ajith Jacob George; Srikanta Ghosh (Tehran University of Medical Sciences, 2018)
Background: We aimed to focus on the ixodid ticks parasitizing wild mammals and reptiles from Wayanad Wildlife Sanctuary, Western Ghat, southern India. Methods: The taxonomic identification of ticks collected from wild mammals and reptiles was performed based on the morphology of adults. Results: We revealed eight species of ticks including, Amblyomma integrum, Rhipicephalus (Boophilus) annulatus, Haemaphysalis (Kaiseriana) spinigera, H. (K.) shimoga, H. (K.) bispinosa, H. (Rhipistoma) indica, Rhipicephalus haemaphysaloides and R. sanguineus  s.l. collected from nine species of wild mammals while four tick species Ablyomma kraneveldi, A. pattoni, A. gervaisi and A. javanense parasitizing on four species of reptiles. The highest host richness was shown by H. (K.) bispinosa and R. haemaphysaloides parasitizing six and five different host species, respectively.  Reports of R. (B.) annulatus on sambar deer, A. javanense and A. kraneveldi on python as well as A. pattoni on Indian rat snake are the new host records from this region. Conclusion: Eight species of ticks parasitizing on nine species of wild mammals and four species of parasitizing on four species of reptiles were identified. The highest host richness was shown by H. (K.) bispinosa and R. haemaphysaloides. H. spinigera as the vector of KFD was also identified in this study.